Effect of Childbirth Education Program on Maternal Anxiety: A Randomized Controlled Trial Using Roy's Adaptation Model - Meei-Ling Gau; Chien-Huei Kao; Chieh-Yu Liu; Su-Yu Kuo; Jen-Jiuan Liaw; Endang Koni Suryaningsih (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Globally, 5.1 - 37.5 % of mothers suffer from anxiety during pregnancy due to adaptation problems. Childbirth education could enhance knowledge and skills to help mothers prepares to cope with adaptation. However, in Indonesia, the manner program provided following nursing theory as a framework has been absent. Objective: To test the effectiveness of childbirth education program based on Roy's Adaptation Model on maternal anxiety Methods: A randomized controlled trial using a computer random allocation block to allocate participants from five health centers in Yogyakarta has been performed. Pregnant women in the experimental group received a modified childbirth education program in four consecutive weeks comprised of lecturing, counseling, brainstorming, and practicing some essential skills for cope adaptation. A self-developed questionnaire was used to assess the demographic data set, Pregnancy-Related Anxiety Questionnaire-Revised was completed to measure the maternal anxiety during pregnancy. An independent t-test and ANCOVA were used to analyze the data.  Results: A total of 87 pregnant women were analyzed (experimental, n= 52, control, n=35), with a mean age of 23. 92 (SD = 1.89), and 29.14 (SD = 2.10), respectively. After the intervention, the score of maternal anxiety had significantly lower in the experimental group compared with the control group (p < .001). In the T-test analysis, the demographic variables were not related to maternal anxiety. Conclusion: Based on the findings, a modified childbirth education program focus on adaptation change based on nursing theory was effective to decrease maternal anxiety during pregnancy. However, what  the participant perceived in the prenatal education program is one of the salient limitations in this study.